Optimization of branching pipelines on basis - Kizilova, N. (My University, 2004)
Structure of the optimal rectangular microcirculatory cell of a leaf is investigated on the model of liquid motion through the bifurcating tubes with permeable walls and its filtration into the cell filled with anisotropic porous biological medium. The relation between the diameters of the tubes in the bifurcation as well as coordinates of the bifurcation point at given width and length of the cell which provides minimum total energy consumptions are obtained.
Keywords: оptimal networks; design principles; Murray’s law; computational methods